The Role of Family Phenomena in Children and Adolescents With Attention Deficit Hyperactivity Disorder. Issue 1 (18th December 2014) - Paidipati, Cynthia P.; Deatrick, Janet A.
Abstract : Topic: Previous research suggests that families are integral to the understanding of children and adolescents with attention deficit hyperactivity disorder (ADHD). Purpose: The purpose of this article is to identify family phenomena related to children and adolescents with ADHD and highlight research findings that intersect family phenomena with the care and treatment of ADHD in youth. Sources: A literature review was conducted at the University of Pennsylvania in spring of 2014 using an online library system. The four major databases utilized are Cumulative Index to Nursing and Allied Health Literature (CINAHL), Ovid Medline, Scopus, and Psyc‐INFO. Conclusions: A wide array of family‐related concepts are identified in the literature and represent a multifaceted and dynamic range of family phenomena related to ADHD youth. Four major themes emerged in the literature, including family stress and strain, parenting practices and caregiver health, family relationships, and family processes related to ADHD management. Different cultural and ethnic groups are reflected in the studies, but the majority of participants are self‐identified Caucasian. As a collective, the research findings suggest family‐related phenomena are essential and relevant to the investigation of children and adolescents with ADHD and worthwhile to explore in future research endeavors, especially in diverse populations.